2018
DOI: 10.2147/dddt.s172068
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of a fixed-dose combination of nimesulide/pantoprazole compared to naproxen/esomeprazole for pain relief in patients with osteoarticular diseases and dyspeptic symptoms

Abstract: PurposeThis study investigated the safety and efficacy of fixed-dose combination tablets of naproxen/esomeprazole magnesium and nimesulide/pantoprazole to determine if both regimens are equally suited to relieve pain in patients with osteoarticular diseases and dyspeptic symptoms.MethodsPatients were randomly assigned to receive either nimesulide/pantoprazole (100 mg/20 mg) twice daily or naproxen/esomeprazole magnesium (500 mg/20 mg) twice daily for 14 days. The primary endpoint was defined as the mean change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…These features are particularly requested in the treatment of diseases such as cancer (Piccolo et al, 2015; Eitsuka et al, 2016; Losson et al, 2016; Zhang et al, 2018) and AIDS (Schader et al, 2011; Excler et al, 2011; Brown et al, 2015; He et al, 2018). However, chronic inflammatory conditions, such as RA and OA may require the same approach: in fact due the clinical characteristics of the disease and to the potential toxicity of available pharmacological treatments, patients would benefit from therapeutic strategies that maximize the clinical efficacy and, at the same time, minimize the associated drug adverse events (Kwon et al, 2018; Lu et al, 2018; Scheinberg et al, 2018; Smith and Cooper-DeHoff, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These features are particularly requested in the treatment of diseases such as cancer (Piccolo et al, 2015; Eitsuka et al, 2016; Losson et al, 2016; Zhang et al, 2018) and AIDS (Schader et al, 2011; Excler et al, 2011; Brown et al, 2015; He et al, 2018). However, chronic inflammatory conditions, such as RA and OA may require the same approach: in fact due the clinical characteristics of the disease and to the potential toxicity of available pharmacological treatments, patients would benefit from therapeutic strategies that maximize the clinical efficacy and, at the same time, minimize the associated drug adverse events (Kwon et al, 2018; Lu et al, 2018; Scheinberg et al, 2018; Smith and Cooper-DeHoff, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported negative experience with the use of antiosteoporotic drugs, which have not shown significant efficacy and the presence of some side effects [31][32][33][34][35][36]. This further encouraged us to undertake our preliminary investigation with the use of alternative treatments to traditional drugs, based on natural substances, on a group of patients, to test their efficacy and tolerability.…”
Section: Criticism Of Traditional Pharmacological Therapiesmentioning
confidence: 99%